2001
DOI: 10.1046/j.1570-7458.2001.00814.x
|View full text |Cite
|
Sign up to set email alerts
|

Flower nitrogen status and populations of Frankliniella occidentalis feeding on Lycopersicon esculentum

Abstract: In a 2‐year study, we manipulated flower chemistry of field grown Lycopersicon esculentum in North Florida and examined subsequent effects on populations of Frankliniella occidentalis. We examined variation in amino‐acid profiles and total nitrogen concentrations of flowers, flower number and plant size seasonally and in response to variable rates of nitrogen fertilization (202 kg ha−1 and 309 kg ha−1). Populations of F. occidentalis sampled every 6 to 10 days were then related to seasonal and treatment effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(55 citation statements)
references
References 21 publications
1
50
0
4
Order By: Relevance
“…Some studies demonstrate that augmented nitrogen fertilizers increase populations of Frankliniella occidentalis Pergande (Thysanoptera: Thripidae) in tomato (Brodbeck et al, 2001), Aphis gossypii Glover (Hemiptera: Aphididae) in cotton (Nevo and Coll, 2001), Nilaparvata lugens Stål and Sogatella furcifera Horvath (Hemiptera: Delphacidae) in rice (Lu et al, 2007). Other researchers have shown that populations of Ostrinia nubilaris Hubner (Lepidoptera: Crambidae) (Phelan et al, 1995), Diabrotica virgifera LeConte (Coleoptera: Chrysomelidae) (Moeser and Vidal, 2004) and Peregrinus maidis Ashmead (Hemiptera: Delphacidae) (Wang et al, 2006), increased in maize when fertilized with nitrogen.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies demonstrate that augmented nitrogen fertilizers increase populations of Frankliniella occidentalis Pergande (Thysanoptera: Thripidae) in tomato (Brodbeck et al, 2001), Aphis gossypii Glover (Hemiptera: Aphididae) in cotton (Nevo and Coll, 2001), Nilaparvata lugens Stål and Sogatella furcifera Horvath (Hemiptera: Delphacidae) in rice (Lu et al, 2007). Other researchers have shown that populations of Ostrinia nubilaris Hubner (Lepidoptera: Crambidae) (Phelan et al, 1995), Diabrotica virgifera LeConte (Coleoptera: Chrysomelidae) (Moeser and Vidal, 2004) and Peregrinus maidis Ashmead (Hemiptera: Delphacidae) (Wang et al, 2006), increased in maize when fertilized with nitrogen.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, no effect of levels of N or K on leaves of eggplant with aphids and thrips was detected, what might be explained to low variations on levels of these compounds on leaves of this plant during the experimental period. Several authors have mentioned that high N levels were associated with aphids and thrips infestations on lettuce, tomato and cotton (Kennedy, 1958;Brodbeck et al, 2001;Cisneros and Godfrey, 2001;Nevo and Coll, 2001) being a key factor for increasing number of aphids in cotton (Cisneros and Godfrey, 2001). However, Leite et al (1999) showed no effect of 100 and 300 mg/kg and 0 and 200 mg/kg of N and K, respectively, in the soil on attack intensity of M. persicae on L. esculentum and on L. hirsutum f. glabratum (PI 134417) in greenhouse.…”
Section: Discussionmentioning
confidence: 99%
“…Plant biomass was dried at 42 o C until dry and weighed. Percent C and N from the plant biomass were measured by combustion in Year 3 only (Brodbeck et al, 2001). Total C and N were calculated by multiplying percentage by plant biomass weight.…”
Section: Data Collection and Analysesmentioning
confidence: 99%